(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Active learning is a crucial method for enhancing student engagement and comprehension in secondary education. This article examines a variety of active learning techniques that can create a more interactive and effective educational setting. By analyzing the advantages and methods for implementing these strategies, this paper seeks to equip educators with practical tools to boost student achievement and participation